2014
DOI: 10.1016/j.bone.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lower leg arterial calcifications by high-resolution peripheral quantitative computed tomography

Abstract: Vascular calcifications and bone health seem to be etiologically linked via common risk factors such as aging and subclinical chronic inflammation. Epidemiologic studies have shown significant associations between low bone mineral density (BMD), fragility fractures and calcifications of the coronary arteries and the abdominal aorta. In the last decade, high-resolution peripheral quantitative computed tomography (HR-pQCT) has emerged as in-vivo research tool for the assessment of peripheral bone geometry, densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
4
24
0
5
Order By: Relevance
“…In diabetic patients, VC is commonly seen in coronary and vascular arteries of lower limbs ( 177 , 178 ). Monckeberg already described medial artery calcification in an autopsy series that was identified in older age, renal failure, and diabetes as the factors associated with calcifications ( 179 ).…”
Section: Key Cellular and Molecular Eventsmentioning
confidence: 99%
“…In diabetic patients, VC is commonly seen in coronary and vascular arteries of lower limbs ( 177 , 178 ). Monckeberg already described medial artery calcification in an autopsy series that was identified in older age, renal failure, and diabetes as the factors associated with calcifications ( 179 ).…”
Section: Key Cellular and Molecular Eventsmentioning
confidence: 99%
“…In addition, HR-pQCT images were reviewed for the presence of vascular calcifications, which were defined as linear or tubular hyperdensity zones of circular, semi-circular, or crescent-like shape, which corresponded to the anatomical territory of the anterior tibial artery, the posterior tibial artery, the radial artery, the ulnar artery, the interosseous branches, or smaller intramuscular or subcutaneous arterioles [34]. Skin calcifications or other non-vascular soft tissue calcifications were not included.…”
Section: Methodsmentioning
confidence: 99%
“…China has the highest number of people with diabetes, which accounts for about one-third of the total number of diabetic patients worldwide [1]. Patients with diabetes commonly manifest vascular calcification, including intima and medial calcification, which are mainly distributed in the coronary artery and lower extremity vessels, respectively [2, 3]. A multi-center epidemiological study demonstrated that the risk of acute cardiovascular events in patients with calcification score >300 is significantly higher than those in patients with calcification score of 1–100 [4, 5].…”
Section: Introductionmentioning
confidence: 99%